Pelatihan Slow Stroke Back Massage (SSBM) sebagai Terapi Non Farmakologis untuk Meningkatkan Kualitas Tidur Lansia dengan Gangguan Tidur - Yuni Fitriyah Ningsih; Joesoef Roepajadi; A Burhanuddin Kusuma Nugraha; Mochamad Azhar Ilmi; Indra Himawan; Elisa Dwi Ratna Sari; Moh. Zein Muttaqin (Laksana Olahraga, 2026)
The number of elderly people increases every year, creating challenges in maintaining health and quality of life, particularly related to sleep disorders that are commonly experienced. This Community Service Program (CSP) was conducted at Sasana Healthy Kranji Community, Paciran District, Lamongan Regency, with the aim of improving the sleep quality of the elderly through Slow Stroke Back Massage (SSBM) training as a non-pharmacological therapy. The methods used included socialization, demonstration, and hands-on practice with the elderly and their caregivers. The evaluation results showed that the activity ran well and received positive responses, with an average participant satisfaction score of 4.3 out of 5. Participants reported that SSBM provided relaxation effects, reduced muscle tension, and helped them sleep more soundly. This activity proves that SSBM training is effective, easy to implement, and beneficial for improving the well-being of the elderly through a community-based non-pharmacological approach.